SISTEM INFORMASI ONLINE PENGOLAHAN DATA SEMINAR DAN WORKSHOP (SEWOPI) HIMAFORTIKA PROGRAM STUDI PENDIDIKAN INFORMATIKA STKIP PGRI SUMATERA BARA - Rio Junaidi (Universitas PGRI Sumatera Barat, 2021)
Information Systems can contribute to HIMAFORTIKA to facilitate the management and data processing of online seminars and workshops that exist in Informatics Education Studies Program, so this system is very important in providing information seminars and workshops to the parties in need and is also one of the tools Aids decision-making for the leadership of the study program or institution, in the management of seminars and workshops as indicators of data management seminar and workshop activities in overcoming the lack of data reporting seminars and workshops.This system is an online application program, which describes data management seminars and workshops in HIMAFORTIKA for the need of quality information, fast, precise and accurate to be reported to the head of study program andinstitutions. This system monitors through a Personal Computer (laptop) with a web interface that has been designed. Performed through computer network access with system Local Area Network (LAN)